2007
DOI: 10.1007/s00198-007-0375-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second hip fractures. A population-based study

Abstract: There is a high incidence of second hip fractures. Secondary prevention of hip fractures needs to be improved. In addition to adequate treatment for osteoporosis, more attention should be directed toward appropriate use of psychotropic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 30 publications
7
75
3
3
Order By: Relevance
“…Patients with hip fracture are at high risk for new vertebral and non-vertebral fractures shortly after the incident hip fracture [7][8][9][10] and represent an important population to target for secondary prevention especially when an adequate time between the first and second hip fractures for interventions has elapsed [10]. Nevertheless, there is little information about the efficacy of osteoporosis therapies in elderly population with established osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with hip fracture are at high risk for new vertebral and non-vertebral fractures shortly after the incident hip fracture [7][8][9][10] and represent an important population to target for secondary prevention especially when an adequate time between the first and second hip fractures for interventions has elapsed [10]. Nevertheless, there is little information about the efficacy of osteoporosis therapies in elderly population with established osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hip fracture survivors have a tremendous high risk for subsequent skeletal fractures with and standardized incidence ratio ranking from 2.8 to 8.1 in men and from 2.1 to 3.9 in women [7,8]. Recently, the cumulative incidence of a second hip fracture in a Finnish cohort has been set in 5.08% at 1 year and 8.11% at 2 years after the first fracture [9]; a similar study from the Framingham Study cohort has shown a 14.8% re-fracture rate during a median of 4.2 years of follow-up, the 1-year mortality being significantly increased after the second hip fracture (24.1% vs 15.9%) [10]. This high rate of subsequent fractures has been related to the high rate of bone loss-5% to 7% during the first year after the fracture [11]-nevertheless, the influence of osteoporosis undertreatment in patients with hip fracture is a fact that cannot be neglected [12][13][14], especially when enough time between the first and second hip fractures for interventions aimed to reduce second hip fractures has elapsed [10].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] However, previous reports indicate that second hip fractures account for up to 15% of all hip fractures. [10][11][12][13][14][15][16][17][18][19] These second hip fractures are associated with poorer postoperative outcomes, including complications, 20 transitions to long-term care 20 and mortality. 21 Omsland and colleagues 22 reported that the number of patients surviving first hip fracture surgery increased over 10 years.…”
mentioning
confidence: 99%
“…In literature, the incidence of a contralateral hip fracture in elderly osteoporotic patients ranges from 7 to 12% within two years after the first femoral neck fracture, with a high percentage of symmetry between the two fractures which varies from 70 to 83% (13,14). Therefore it is mandatory to adopt appropriate strategies to prevent the second fracture in these patients.…”
Section: Prevention Of the Second Contralateral Femoral Neck Fracturementioning
confidence: 99%